ERRATUM: Formal description of Protosticta nigra spec. nov. from Vietnam - Kompier, Tom (Zootaxa, 2016)
Regrettably I neglected to indicate the type series for one of the new species described in Kompier (2016). Fixation of a holotype, or syntypes, is compulsory for names published after 1999 (ICZN 1999, Article 16.4.1). I am doing so here as a necessary element to validate the species description. The published paper contains a diagnosis and illustrations for the species. The diagnosis is repeated here for formal reasons. The name Protosticta nigra is thus only available from the present publication.      I thank Jan van Tol and Dennis Paulson for their assistance.